Developing a Model for the Evaluation of Iranian EFL Teachers' Awareness of the Code of Ethics in Research - Farideh Samadi; Khalil Motallebzadeh; Hamid Ashraf; Gholam Hassan Khajavy (National Research University Higher School of Economics, 2020)
Conducting educational research is not an arbitrary practice. When implementing educational research, teachers, as researchers, need to adhere to ethical rules and norms. Thus, developing an instrument for evaluating English as foreign language (EFL) teachers' awareness of the code of ethics in research can guide Iranian ELT professionals to work towards setting standards in the assessment of Iranian EFL teachers' professional development and may assure consistency in EFL teachers' quality assurance. The principal determination of the present study was to develop a scale to evaluate EFL teachers' awareness of the code of ethics for conducting research in Iran. This work's theoretical framework is based on the most influential ethical issues and elements in research in Samadi, Motallebzadeh, Ashraf, and Khajavy's (2020) study. To this end, 272 Iranian EFL teachers (chosen using convenience sampling) participated in the analysis to fill out the scale in the piloting stage. The scale consisted of five main categories: (F1) Before the beginning of the research, (F2) the Beginning of the research, (F3) Gathering the data, (F4), Analyzing the data, and (F5) Writing, reporting, sharing, and storing the data. The first draft of the scale consisted of 60 items. As part of the validation procedure, the reliability of this scale was determined through Cronbach's alpha, and its validity was measured by running a confirmatory factor analysis (CFA) through a structural equation modeling approach. After performing the CFA, it was found that the questionnaire had high construct validity. Finally, the statistical findings were presented, and the implications of the ELT domain were given. The findings provide empirical evidence that provides a framework for assessing and evaluating EFL teachers' awareness of the code of ethics in research.